International Day of Forest 2019 - Reforestation - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Wale Awoyemi, Manager, IITA Forest Center speaking on "Reforestation" at the International Day of Forest 2019 at IITA Ibadan.